Growth And Yield Of Tomato Plants(Lycopersicum esculentum Mill) Servo F1 Varieties Due To Application Of Soil Soil Destruction (Novelgro Terra) And Reduction Of Npk Fertilizer Dosage - alwi hasan; Agus Sugianto; Mahayu Woro Lestari (AGRONISMA, 2022)
Researchto   find out the  influence   of   soil-fixing   applications that are  expected to facilitate  the  availability  of nutrients,  and  soil quality  so as  to  reduce the amount of  inorganic  fertilizer  use  and  improving the  quality of  tomato plant  production.  This research was conducted on the  land area of Merjosari Village of Malang City and Integrated Laboratory of the Faculty of Agriculture, Universitas Islam Malang. The study was conducted  on 01  Maret until August 1, 2021. The research design used is a Factorial   Randomized  Group  Design  (RAK)  consisting  of  two  factors,  with  12  treatments  and 3  repeats. The results showed that the  parameters of the plant's height, the number  of  leaves, the area of  the leaves  at the age of  28  hst had a noticeable effect.  In  the yield  of  soil-fixing    plants  of 0.5 ml / liter of water was able to  reduce the use of  NPK  fertilizer by 50% on  variable fruit set yields of 59.72% and  the number of  harvested fruit    with  a value of  19.58  pieces/ton. At  harvest weight, the  treatment of K1P3 (bio-soil destruction    0.5 ml / liter of water +  NPK fertilizer 50%) is able to  increase  by  17.28 tons / ha.